An examination of the relationship between athlete leadership and cohesion using social network analysis. Issue 21 (1st November 2016) - Loughead, Todd M.; Fransen, Katrien; Van Puyenbroeck, Stef; Hoffmann, Matt D.; De Cuyper, Bert; Vanbeselaere, Norbert; Boen, Filip
ABSTRACT: Two studies investigated the structure of different athlete leadership networks and its relationship to cohesion using social network analysis. In Study 1, we examined the relationship between a general leadership quality network and task and social cohesion as measured by the Group Environment Questionnaire (GEQ). In Study 2, we investigated the leadership networks for four different athlete leadership roles (task, motivational, social and external) and their association with task and social cohesion networks. In Study 1, the results demonstrated that the general leadership quality network was positively related to task and social cohesion. The results from Study 2 indicated positive correlations between the four leadership networks and task and social cohesion networks. Further, the motivational leadership network emerged as the strongest predictor of the task cohesion network, while the social leadership network was the strongest predictor of the social cohesion network. The results complement a growing body of research indicating that athlete leadership has a positive association with cohesion.